2017 Energy Sector : Private Participation in Infrastructure - World Bank Group (World Bank, Washington, DC, 2018)
In 2017, PPI investments in energy stood at USD 51.9 billion across 203 projects (compared to USD 46.8 billion across 183 projects in 2016), and accounted for more than half (56 percent) of the PPI investments across all four infrastructure sectors included in the PPI database—energy, water, transport and ICT. Of these four, the energy sector has attracted the most private-sector participation. By dollar value, from 2008 to 2017, cumulative investments in the energy sector (conventional and renewable energy) accounted for approximately 59 percent of total PPI investments. Although the energy sector continued to be the predominant sector attracting private investments in 2017, because of increased investment in other sectors, the share of energy-sector investments decreased from 69 percent of all PPI investments in 2016 to 56 percent in 2017.Energy investments reached their peak in 2012, as private investors shrugged off the effects of the global financial crisis and pumped USD 89.6 billion into the sector. However, by 2015, private-sector investments in energy reached their lowest levels, at USD 38.5 billion, a trend largely accelerated by a steep drop in oil prices in 2014 and a subsequent decrease of investment in the conventional-energy sector. From 2015 to 2017, investments picked up gradually, with increasing investments in renewables.In terms of the number of projects, two-thirds of all projects (203 out of 304) in 2017 were in the energy sector. Interestingly, the number of energy projects as a percentage of all PPI projects fluctuated very little after 2014. On average, from 2008 to 2017, the PPI energy projects accounted for 69 percent of all PPI projects.